G Protein-Coupled Receptor-Mediated Mitogen-Activated Protein Kinase Activation through Cooperation of Gα(q) and Gα(i) Signals - Blaukat, Andree (American Society for Microbiology, 2000)
G protein-coupled receptors (GPCRs) have been shown to stimulate extracellular regulated kinases (ERKs) through a number of linear pathways that are initiated by G(q/11) or G(i) proteins. We studied signaling to the ERK cascade by receptors that simultaneously activate both G protein subfamilies. In HEK293T cells, bradykinin B(2) receptor (B(2)R)-induced stimulation of ERK2 and transcriptional activity of Elk1 are dependent on Gα(q)-mediated protein kinase C (PKC) and on Gα(i)-induced Ras activation, while they are independent of Gβγ subunits, phosphatidylinositol 3-kinase, and tyrosine kinases. Similar results were obtained with m(1) and m(3) muscarinic receptors in HEK293T cells and with the B(2)R in human and mouse fibroblasts, indicating a general mechanism in signaling toward the ERK cascade. Furthermore, the bradykinin-induced activation of ERK is strongly reduced in Gα(q/11)-deficient fibroblasts. In addition, we found that constitutively active mutants of Gα(q/11) or Gα(i) proteins alone poorly stimulate ERK2, whereas a combination of both led to synergistic effects. We conclude that dually coupled GPCRs require a cooperation of Gα(i)- and G(q/11)-mediated pathways for efficient stimulation of the ERK cascade. Cooperative signaling by multiple G proteins thus might represent a novel concept implicated in the regulation of cellular responses by GPCRs.